Association of years to parent's sporadic onset and risk factors with neural integrity and Alzheimer biomarkers. (13th October 2020) - Arenaza-Urquijo, Eider M.; Salvadó, Gemma; Operto, Gregory; Minguillón, Carolina; Sánchez-Benavides, Gonzalo; Crous-Bou, Marta; Grau-Rivera, Oriol; Sala-Vila, Aleix; Falcón, Carles; Suárez-Calvet, Marc; Zetterberg, Henrik; Blennow, Kaj; et al.
Abstract : Objective: To evaluate the hypothesis that proximity to parental age at onset (AAO) in sporadic Alzheimer disease (AD) is associated with greater AD and neural injury biomarker alterations during midlife and to assess the role of nonmodifiable and modifiable factors. Methods: This observational study included 290 cognitively unimpaired (CU) participants with a family history (FH) of clinically diagnosed sporadic AD (age 49–73 years) from the Alzheimer's and Families (ALFA) study. [ 18 F]flutemetamol-PET standardized uptake value ratios, CSF β-amyloid42/40 ratio, and phosphorylated tau were used as AD biomarkers. Hippocampal volumes and CSF total tau were used as neural injury biomarkers. Mental and vascular health proxies were calculated. In multiple regression models, we assessed the effect of proximity to parental AAO and its interaction with age on AD and neural injury biomarkers. Then, we evaluated the effects of FH load (number of parents affected), sex, APOE ε4, education, and vascular and mental health. Results: Proximity to parental AAO was associated with β-amyloid, but not with neural injury biomarkers, and interacted with sex and age, showing that women and older participants had increased β-amyloid. FH load and APOE ε4 showed independent contributions to β-amyloid load. Education and vascular and mental health proxies were not associated with AD biomarkers. However, lower mental health proxies were associated with decreased hippocampal volumes with age. Conclusion: The identification of the earliest biomarker changes and modifiable factors to be targeted in early interventions is crucial for AD prevention. Proximity to parental AAO may offer a timeline for detection of incipient β-amyloid changes in women. In risk-enriched middle-aged cohorts, mental health may be a target for early interventions. ClinicalTrials.gov identifier: NCT02485730. Classification of evidence: This study provides Class II evidence that in CU adults with FH of sporadic AD, proximity to parental AAO was associated with β-amyloid but not with neural injury biomarkers.